Numerical analysis on the effect of built form in urban ventilation assessment / Mohd Azhari Mohd Rodzi - Mohd Rodzi, Mohd Azhari (2016)
Urban ventilation refers to process of supplying air into urban canopy layer (UCL) and distributing it within the layer. However, potential for urban ventilation will be lessen for urban areas that receive low annual mean wind velocity. Mean flow around heterogeneous built form of Kuala Lumpur was analyzed numerically by using RNG k-Ɛ model as means to assess urban ventilation. Three built forms were used in present study, which are low-dense built form of Kampung Baru, medium-dense built form of Taman Keramat and high-dense built form of Pantai Dalam, and their density were characterized based on packing density of frontal area ratio. Since highly dense built form is characterized with deep street canyon, the mean flow pattern around the built form is dominated by skimming flow. Also, turbulence fluctuation was found to play important role in exchange processes to remove pollutant at UCL height as the flow turn becoming fully developed. Urban ventilation for the built form is assessed by using two ventilation indices of wind velocity ratio (VR) to evaluate the wind availability for pedestrian wind environment and normalized flow rates (Q*) to examine the wind permeability across the UCL volume. Magnitude of VR at pedestrian-level was found to decline as the packing density of the built form increases. Low magnitude of VR signified inadequate wind availability for pedestrians, especially in high-dense built form of Pantai Dalam since VR for most regions at the built form is below 0.12. An exponential equation to predict VR that was derived from rectangular block arrays was verified to be unsuitable for built form. Contribution of breezeway was observed to be vital in allowing wind penetration for urban ventilation in high density built form, which implied by high Q*. Suggestions were provided from results of the assessment and expected to be useful in improving urban ventilation design.